Applying Fuzzy Logic to Measure the Intensity of Volunteering Intentions: A Study on Intrinsic and Extrinsic Motivations in Organizational Behavior (Journal of Asian Development Studies, 2025)
Organisational behaviour theories aim to improve employees' efficiency and consistent productivity. This study introduced intrinsic motivation of individual volunteering intentions based on trigger and religion, whereas extrinsic motivation consists of instrumental and social intention modes. The performance of an individual depends upon the inner energetic force, which will incorporate intention, direction and intensity of work. Organizations are involved with volunteer work that requires motivation to participate and sustain in auxiliary activities. Individuals with volunteer motivation have a goal and direction: to measure the intensity of their motivational work using fuzzy logic. With the help of fuzzy logic, which proposes and rationally determines the intensity, this study has provided a logical and visual depiction of volunteering intention.